2009
DOI: 10.1029/2009gl039887
|View full text |Cite
|
Sign up to set email alerts
|

First observations of large‐scale wave structure and equatorial spread F using CERTO radio beacon on the C/NOFS satellite

Abstract: First observations of large‐scale wave structure (LSWS) and the subsequent development of equatorial spread F (ESF), using total electron content (TEC) derived from the ground based reception of beacon signals from the CERTO (Coherent Electromagnetic Radio Tomography) radio beacon on board C/NOFS (Communications/Navigation Outage Forecasting System) satellite, are presented. Selected examples of TEC variations, using measurements made during January 2009 from Bac Lieu, Vietnam (9.2°N, 105.6°E geographic, 1.7°N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
113
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 100 publications
(131 citation statements)
references
References 26 publications
17
113
0
1
Order By: Relevance
“…There have been many studies on the occurrence characteristics of ionospheric density irregularities using groundbased measurements (Rastogi, 1980;Abdu, 2001), satellitebased in situ measurements (Watanabe and Oya, 1986;Huang et al, 2002;Burke et al, 2004), and topside sounders (Maruyama and Matuura, 1984), and many important features of these have been reported including temporal variations (Sahai et al, 2000;Huang et al, 2002), seasonallongitudinal variability (Burke et al, 2004), several-day variation, and day-to-day variation (Basu et al, 1996) though several enigmatic features of them are yet to be revealed (Thampi et al, 2009). However, studies on continuous and global characteristic features of ionospheric plasma irregularities are very scanty due to the fact that the global coverage is difficult to obtain from ground-based observations.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies on the occurrence characteristics of ionospheric density irregularities using groundbased measurements (Rastogi, 1980;Abdu, 2001), satellitebased in situ measurements (Watanabe and Oya, 1986;Huang et al, 2002;Burke et al, 2004), and topside sounders (Maruyama and Matuura, 1984), and many important features of these have been reported including temporal variations (Sahai et al, 2000;Huang et al, 2002), seasonallongitudinal variability (Burke et al, 2004), several-day variation, and day-to-day variation (Basu et al, 1996) though several enigmatic features of them are yet to be revealed (Thampi et al, 2009). However, studies on continuous and global characteristic features of ionospheric plasma irregularities are very scanty due to the fact that the global coverage is difficult to obtain from ground-based observations.…”
Section: Introductionmentioning
confidence: 99%
“…Struktur seakan gelombang tersebut berpunca daripada perolakan AGW daripada lapisan troposfera (Shiokawa et al 2006;Singh et al 1997) yang seterusnya membentuk LSWS (Ram et al 2014;Thampi et al 2009;Tsunoda 2015). Kehadiran LSWS di bawah permukaan lapisan ionosfera telah dipertimbangkan sebagai punca pembentukan PBB.…”
Section: Perbincanganunclassified
“…The paucity of LSWS data, until now, stems directly from using the wrong kinds of instruments to study ESF seeding. Indeed, LSWS has now been detected and described with TEC measurements using the radio beacons on the C/NOFS satellite [e.g., Thampi et al, 2009;Tsunoda et al, 2010Tsunoda et al, , 2011Tulasi Ram et al, 2012], as zonally varying spatial structures. Moreover, we have shown that LSWS is more or less stationary by comparing the TEC pattern found in successive passes of C/NOFS , and we have shown that this behavior is exactly as expected from our understanding of equatorial electrodynamics.…”
Section: Paucity Of Lsws Datamentioning
confidence: 99%
“…We have shown for the first time that LSWS characteristics can be extracted from TEC measurements using radio beacons on board an equatorial-orbiting satellite [Thampi et al, 2009;Tsunoda et al, 2010;Tulasi Ram et al, 2012]. Before C/NOFS TEC measurements, only beacons on polar-orbiting satellites had been used to obtain information about plasma structure as a function of latitude.…”
Section: Lsws Characteristics From Tec Measurementsmentioning
confidence: 99%
See 1 more Smart Citation